2022
DOI: 10.17338/trainology.11.2_22
|View full text |Cite
|
Sign up to set email alerts
|

Changes in strength and jump performance over a 10 week competitive period in male collegiate golfers

Abstract: As with most structured training programs to enhance performance, a reduction in resistance training volume is seen during competitive periods and an emphasis is placed on technical and tactical training. For that reason, it is important to know where priorities should be placed during times of reduced physical preparation training and if the sport itself allows for the maintenance of neuromuscular qualities.Objective: Thus, the purpose of this investigation was to examine changes in strength and jump testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…Third, future studies should consider undertaking some individual data analyses, given golf is an individual sport, which has been performed in a recent publication in golf (14). Unsurprisingly, sample sizes in golf studies are often small, which is likely to result in them being underpowered.…”
Section: Discussionmentioning
confidence: 99%
“…Third, future studies should consider undertaking some individual data analyses, given golf is an individual sport, which has been performed in a recent publication in golf (14). Unsurprisingly, sample sizes in golf studies are often small, which is likely to result in them being underpowered.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, single-subject analyses were performed on each variable of interest to determine if the changes seen were outside the individual variability exhibited during the pretest. Variability was assessed using pretest CV values [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…During periods in which collegiate golfers are competing, physical preparation commonly becomes less of a priority as sport-specific training increases. Recently, Donahue et al (Donahue, Peel, Shelby A, et al, 2022) showed that during a 10-week competitive period, male collegiate golfers maintained or improved vertical jump performance, while reductions were present in isometric midthigh pull values. Interestingly, a single-subject analysis was also completed with this investigation and showed that group mean changes did not match individual changes, as several individuals saw reductions in vertical jump performance that were masked by others who saw improvement (Donahue, Peel, Shelby A, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Donahue et al (Donahue, Peel, Shelby A, et al, 2022) showed that during a 10-week competitive period, male collegiate golfers maintained or improved vertical jump performance, while reductions were present in isometric midthigh pull values. Interestingly, a single-subject analysis was also completed with this investigation and showed that group mean changes did not match individual changes, as several individuals saw reductions in vertical jump performance that were masked by others who saw improvement (Donahue, Peel, Shelby A, et al, 2022). In female golfers, only one study investigated the association between CHS and vertical jump performance (Coughlan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation